Different Workplace Currencies and Employee Voice: From the Multidimensional Approach of Leader–Member Exchange - Zhou, Qiwei; Huo, Da; Wu, Fan (Frontiers in Psychology, 2020)
Building upon social exchange theory and the current voice research, we posit that employee workplace “currencies of exchange” with the leader (i.e., social currency and work-related currency) are key predictors of employee promotive and prohibitive voice. Furthermore, we distinguish between the different roles of social currency and work-related currency in predicting promotive and prohibitive voice, respectively. More importantly, this study further explores the moderating effects of two important individual characteristics, psychological safety and power distance orientation, on the relationships between currencies and voice. We sampled 128 employees from the headquarter of a large bank in China. Our results show that both social currency and work-related currency are determinants of promotive and prohibitive voice. Moreover, the boundary conditions for the two kinds of currencies are different. Specifically, employee psychological safety strengthens the influence of social currency on both types of employee voice, while employee power distance orientation could only amplify the relationship between work-related currency and promotive voice. Our research provides important implications for both theory and practice. Limitations and future directions are also discussed.